Access to Information for Farm-Level Decision-Making. Issue 4 (1st October 2016) - Drafor, Ivy
ABSTRACT: Radio is an important medium for conveying agricultural information among farmers in remote areas. This study assessed the channels of information available to four farming communities in Ghana and analyzed stakeholder networks in information generation and dissemination. About 50% of the farmers expressed a willingness to pay for relevant information, though they think general farm information should be free to all. Farmers ranked other farmers as their most important and least expensive sources. Farm-level decision-making requires timely, adequate, and appropriate information, which can bring smallholder farmers closer to their world competitors through increased production, effective marketing, and increased incomes.